Exploring Brunei’s Oral Traditions: A Review of Cerita Lisan Brunei (International Journal of Linguistics and Indigenous Culture, 2024)
This article reviews Cerita Lisan Brunei, a compilation of 50 folklore stories from Brunei Darussalam’s four districts: Brunei-Muara, Belait, Tutong, and Temburong. Produced by Universiti Brunei Darussalam students in the early 1990s, the book represents a significant effort to preserve Brunei’s oral heritage amidst evolving socio-cultural dynamics. This review uses qualitative descriptive analysis to examine the folklore types featured in the book—myths, legends, fables, and allegories—and evaluates its strengths and weaknesses. The book effectively highlights Brunei's cultural and historical legacy thus making it suitable for teaching and learning materials. It also contributes meaningfully to preserving Brunei’s unwritten oral traditions. However, the absence of original language transcriptions and limited contextual notes for historical and fictional stories need improvement. Adding these elements would enhance the book’s historical accuracy and reader comprehension. Despite these shortcomings, Cerita Lisan Brunei remains a valuable resource for readers of all levels, from primary to university. It would serve as an essential platform for preserving and sharing Brunei’s oral folklore tradition.